Effect of Soaking Time of Starfruit Extract (Averrhoa Bilimbi L) on Compressive Strength of Nanohybrid Composite Resin - Fauziah Rachmawati; Biancha Sri (Cigarskruie: Journal of Educational and Islamic Research, 2023)
Starfruit is a popular fruit because of its sour nature. The acidic nature of starfruit, with an acidic pH of 1-2, has an effect on restoration materials. Compressive strength is a mechanical property of nanohybrid composite resin that is a requirement for successful long-term restoration. Composite resins have their own limitations, such as the physical properties of liquid absorption, which result in the degradation of the matrix polymer network due to exposure to drinks with an acidic pH. This research aims to determine the effect of soaking time on the compressive strength of nanohybrid composite resin soaked in starfruit extract. This type of research is laboratory experimental with a true experimental design and a posttest-only control group design. The sample is cylindrical, with a diameter of 5 mm and a thickness of 4 mm. The treatment groups in this study consisted of the nanohybrid composite resin group soaked in starfruit extract for 9, 27, and 54 hours and the control group treated without soaking. Testing using the Universal Testing Machine tool. Data were analyzed using One Way Anova. The one-way Anova test obtained a significance value of 0.003 (p<0.05), so the research hypothesis was accepted. There was a decrease in the compressive strength of the nanohybrid composite resin soaked in starfruit extract.